2020
DOI: 10.2151/jmsj.2020-058
|View full text |Cite
|
Sign up to set email alerts
|

Clausius-Clapeyron Scaling of Extremely Heavy Precipitations: Case Studies of the July 2017 and July 2018 Heavy Rainfall Events over Japan

Abstract: The usefulness of Clausius-Clapeyron (CC) scaling in explaining extremely heavy precipitations is explored in the present-day climate and in pseudo-global-warming (PGW) conditions. This is analyzed by conducting regional-scale numerical simulations at 1-km grid resolution for two recent extreme rainfall events that occurred in Japan: the case in northern Kyushu during 5 -6 July 2017 and the case in Shikoku Island during 5 -8 July 2018. The Weather Research and Forecasting (WRF) model was used for the simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, we anticipate that specific humidity over the Indian region will rise in response to warming scenario. This increase in specific humidity and upward motion of air could explain the anticipated intensification of rainfall over India under future warming climate conditions [4,[44][45][46][47][48][49][50]. However, it's worth noting that our analysis also revealed weaker vertical motion of air in warming scenario over the Western Ghats areas.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, we anticipate that specific humidity over the Indian region will rise in response to warming scenario. This increase in specific humidity and upward motion of air could explain the anticipated intensification of rainfall over India under future warming climate conditions [4,[44][45][46][47][48][49][50]. However, it's worth noting that our analysis also revealed weaker vertical motion of air in warming scenario over the Western Ghats areas.…”
Section: Discussionmentioning
confidence: 58%
“…No convective parameterization scheme was used in the innermost domain (D03) to represent convective clouds. This study follows the previous studies that examined the same rain event (Kawano and Kawamura, 2020;Nayak and Takemi, 2020) for the choice of the cumulus scheme in the outer and intermediate domains and the nesting method. We have confirmed that the model could not reproduce the amount of precipitation reasonably during the event without the cumulus schemes in these domains.…”
Section: Numerical Modelmentioning
confidence: 99%
“…The literature provides many detailed accounts of the rain event of July 5, 2017 (Kato et al, 2018;Takemi, 2018;Kawano and Kawamura, 2020;Nayak and Takemi, 2020;Tsuji et al, 2020); therefore, only a brief overview is presented here. Figure 3A shows the horizontal distribution of equivalent potential temperature (EPT) and horizontal winds in the lower troposphere, superimposed on the sea-level pressure, derived from the U.S. National Center for Environmental Prediction (NCEP) final analysis (FNL) averaged from 12:00 UTC July 4 to 12:00 UTC July 5, 2017.…”
Section: Event Overviewmentioning
confidence: 99%
“…In terms of future expectations, refs. [33,34] estimated that the intensity and frequency of extreme precipitation associated with the HRE18 and Baiu heavy rainfall will increase under a warming climate in the future. Furthermore, ref.…”
Section: Heavy Rainfall Event In July 2018 In Western Japanmentioning
confidence: 99%
“…Several studies [34,[36][37][38][39][40] have developed meteorological forecasts for the HRE18. Several hydrological studies have been conducted for the HRE18.…”
Section: Heavy Rainfall Event In July 2018 In Western Japanmentioning
confidence: 99%